MEMBANGUN KERJASAMA ANTAR KELUARGA MELALUI POLA ASUH KARAKTER ISLAMI DI LINGKUNGAN MASYARAKAT - Siti Nurhaliza; Abdul Ghofur; Rabiyanur Lubis (LPPM Universitas Islam 45, 2022)
As parents, we must have a way of parenting and methods in the education process of the child. There are several methods in educating children, namely: democratic parenting, permissiveness and authority. And in providing care for children, several strategies are needed to provide education with exemplary methods, habituation, attention, advice and punishment methods. Of course, carrying out parenting and methods in the child's education process has an outline goal, namely to make the process of habituation to good things so that it affects the child's personality in adulthood. The main program is about the impact and how to address the problem of cyberbullying. Maybe this is often taken for granted, even though this can all be very fatal for the victim of cyberbullying. Cyberbullying can happen to anyone, so we all have to take this seriously, so that a safe environment will be formed.